Morphometric study of the diaphysial nutrient foramen of the humerus in the Indore population - Singh, Pawika; Modi, Vimal; Singh, Anand Kumar (International Journal of Research in Medical Sciences, 2023)
Background: The nutrient arteries may be affected to a consequence of fracture/surgical intervention of fracture of the humeral shaft, which may result in nonunion or delayed union of fracture. Number and position of nutrient arteries must be determined. In order to preserve them during any surgical procedure of the humeral shaft, it is therefore essential to be aware of the existence of the nutrient foramen. The primary objective of this research is to identify the number, location, and orientation of nutrient foramina (NF) of humerus. Methods: The study was conducted on 100 dried humeri of unknown gender obtained from department of anatomy, Index Medical College, Indore (M.P), India. The number, location, and direction of NF were observed. Results: One nutrient foramen was present in 77% of humeri, followed by double foramen in 20% of cases and triple foramen in 3% of cases. The anteromedial surface hosted the majority (80.16%) of the NF, followed by the anterolateral (4.76%) and posterior surfaces (15.08%). The middle third of the shaft (96.03%) included the greatest number of NF, followed by the distal third (3.97%). On the distal end of the humerus, there was no nutrient foramen to be observed. All NF were directed downward. Conclusions: The location of the nutrient foramen of the humerus was not constant; it may present on anteromedial, anterolateral, or posterior surfaces. Similarly, it may present on the middle or distal third of the shaft of the humerus. This study will help surgeons planning the surgical intervention of the shaft of the humerus, which will possibly reduce the chances of nonunion or delayed union.